Tiempo de clampaje del cordón umbilical y nivel de hemoglobina del recién nacido en un hospital del seguro social - Iquitos 2022 - Chung Rengifo, Augusto (2023)
The study of the moment in which the clamping of the umbilical cord is carried out and its effect regarding the value of hemoglobin in neonates by eutocic delivery who were born in the hospital III EsSalud Iquitos (a city located in the Peruvian Amazon located at an altitude of 106 m.s.n.m.) during the period from January to December 2022, for this, 689 records of newborns were evaluated with the purpose of finding the impact of the moment in which the umbilical cord clamping is performed on the hemoglobin level. The clamping process was carried out in an average time of 82 seconds, with a minimum time of 10 seconds and a maximum time of 140 seconds. Regarding the clamping time, the newborns were classified into two groups: Early Clamping (during the first 60 seconds) and Late Clamping (after 60 seconds). 39.62% presented a type of early clamping; while 60.38% presented a type of late clamping. Highly significant differences were found, the most frequently used type of clamping was late, with a time that varied between 85 and 105 seconds. 17.71% presented anemia; while 76.63% presented normal hemoglobin; and 5.66% presented polycythemia. The majority of newborns presented normal type hemoglobin, with a level that varied between 17.1 gr/dl and 17.5 gr/dl. Late clamping is more related to the type of normal hemoglobin. On the other hand, when analyzing a possible association between clamping time and other biomedical characteristics (weight, gestational age by Capurro, sex); No associations were found, so these variables are independent, in relation to the clamping time. The hemoglobin level in both sexes has a similar association with clamping time. At the end of the study, considering the results obtained, late clamping is recommended.